2007
DOI: 10.1055/s-2007-995370
|View full text |Cite
|
Sign up to set email alerts
|

Praktische Aspekte der prothetischen Stimmrehabilitation nach Laryngektomie

Abstract: Since the last decade of the last century, surgical voice restoration with the use of voice prostheses has become a standard after total laryngectomy. About 80-90 % of the patients are capable to speak well or even very well with a voice prosthesis. Although severe complications have become rare since special pharynx protectors are in use for the implantation of the voice prostheses, minor problems are quite common. Primarily, these are frequent leakages through the prosthesis caused by fast wear and tear of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 4 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…Moricz et al refer to endoscopy-based balloon dilation as a non-traumatic method that can be easily performed [166]. Delank and Scheuermann recommend manufacturing an individually adjusted Herrmann voice prosthesis in order to bypass the spastic or stenotic pharyngoesophageal area [167]. …”
Section: Voice Prostheses and Their Applicationmentioning
confidence: 99%
“…Moricz et al refer to endoscopy-based balloon dilation as a non-traumatic method that can be easily performed [166]. Delank and Scheuermann recommend manufacturing an individually adjusted Herrmann voice prosthesis in order to bypass the spastic or stenotic pharyngoesophageal area [167]. …”
Section: Voice Prostheses and Their Applicationmentioning
confidence: 99%
“…A loss of valve functionality leads to poor speech and requires replacement of the device (Ticac et al, 2010;Leonhard and Schneider-Stickler, 2015). Moreover, the microbial colonization may act as a reservoir of potential pathogens which, subsequent to aspiration, may lead to life-threatening infections such as pneumonia (Delank and Scheuermann, 2008). The mean VP lifespan is highly variable across different studies and has historically been reported as being between 120 and 200 days (Schafer et al, 2001;Sayed et al, 2012).…”
Section: Introductionmentioning
confidence: 99%